Beneficial effects of silibinin on serum lipids, bile acids, and gut microbiota in methionine-choline-deficient diet-induced mice - Wang, Wei; Zhai, Ting; Luo, Ping; Miao, Xiaolei; Wang, Junjun; Chen, Yong (Frontiers in Nutrition, 2023)
Background and Purpose: Silibinin (SIL) is a flavonoid lignin isolated from the fruit and seeds of silybum marianum, and exhibits good therapeutic potential for NASH. However, the effects of SIL on serum lipids, bile acids (BAs) and gut microbiota (GM) in NASH mice remain unknown. This work aimed to explore the beneficial effects of SIL supplementation on serum lipids, bile acids and gut microbiota in MCD mice. Experimental Approach: After male C57BL/6 mice were fed with methionine-choline deficient (MCD) diet and simultaneously gavaged with SIL (20 mg/kg. d) for 8 weeks, the pathological changes of liver tissue were observed by oil red O, haematoxylin-eosin and Masson tricolour staining, the levels of serum AST,ALT, and liver TG,MDA were detected by assay kits, metabonomics and 16S rDNA sequencing were used to analyse the composition of serum lipids and BAs and the abundance of GM, the mRNA expression levels of hepatic genes related to BAs homeostasis were detected by RT-qPCR. Results: The results indicated that SIL treatment decreased the levels of 26 lipids (including 4 arachidonic acids, 7 FFAs, 12 acyl carnitines and 3 GP), 2 BAs (23-DCA, GLCA) and Dubosiella, increased the levels of 10 lipids (including TxB3, PG16:0_18:1, Cer t18:0/24:0 and 7 TGs ), 5 BAs (β-MCA, α-MCA, UDCA, 3-oxo-DCA and HCA) and 2GM(Verrucomicrobiota and Akkermansiaceae) of MCD mice, but had no significant effect on the mRNA expression of CYP7A1, CYP27A1, Bsep, Mrp2, Ntcp and Oatp1b2. Therefore, influencing GM composition and then regulating the levels of serum lipids and BAs through enterohepatic axis should be an important mechanism of SIL-induced alleviative effect on MCD mice. More importantly, we found that SIL had a good coordination in regulating the abundance of GM and the contents of serum lipids and BAs in MCD mice, that is, when the abundance of probiotics was up-regulated, the content of beneficial unsaturated fatty acids in serum was up-regulated, while the serum levels of harmful lipids and BAs were down-regulated. Conclusion: The alleviating effect of SIL on NASH may be closely related to the correction of intestinal bacteria disorder and serum bile acid, lipid metabolic disturbance in mice.